Democratic practices and youth in political participation: a doctoral study. Issue 1 (31st December 2020) - Saud, Muhammad; Ida, Rachmah; Mashud, Musta'in
ABSTRACT: Youth in democratic activities has changed the political scenario of Pakistan. The current study was aimed to identify the youngsters towards their participation in democratic paractices and political activities. The novelity of presnt study is to introduce a new theory of 'Youth-Inn' which indicated the continuous youth participation and involvement in community problem solving, peers motivation, influence public to do vote, and other political matters. The phenomena of this study are based on the present political scenario of Pakistan and youth participation in building the political structure. The study was quantitative in nature and data were collected through random sampling techniques, hundreds of respondents participated from two provinces of Pakistan, which are Punjab and Khyber Pakhtunkhwa. The objective of the study is to highlight the performance of youth activities, contribution to the political participation, their role in political parties and interests in political and social matters. The findings of the study suggest that youth in Pakistan are increasingly participating in democratic, social and political activities, which are their basic and core responsibility to take apart and do sufficient steps for the country.